Теоретичні аспекти професійної підготовки майбутніх магістрів у сфері техніки та технологій: зарубіжний досвід - Сергій Ящук (Pavlo Tychyna Uman State Pedagogical University, 2015)
У статті здійснено аналіз системи вищої освіти окремих Європейських країн та США в контексті підготовки майбутніх фахівців в сфері техніки та технологій в умовах магістратури. На основі аналізу документів та науково-практичних досліджень вітчизняних та зарубіжних науковців розкрито особливості підготовки майбутніх викладачів з дисциплін техніко-технологічного спрямування у вищих навчальних закладах зарубіжних країн. В статье осуществлен анализ системы высшего образования отдельных европейских стран и США в контексте подготовки будущих специалистов в области техники и технологий в условиях магистратуры. На основе анализа документов и научно-практических исследований отечественных и зарубежных ученых раскрыты особенности подготовки будущих преподавателей по дисциплинам технико-технологического направления в высших учебных заведениях зарубежных стран. The analysis of higher educational system of some European countries and the USA in the context of future technical and technological specialists training at Master's level has been made in the article. The peculiarities of training of future lecturers of technico-technological subjects in foreign higher educational establishments have been investigated on the basis of analyzing documents and scientific and practical research of Ukrainian and foreign scientists. It was also noted that foreign experience of training in the field of technique and technology in terms of Master courses should be carefully examined. It would help to use some scientific ideas in the system of Master training in educational institutions. The author proved that in preparing Masters of technique and technology abroad the requirement of two years studying on the basis of previously obtained bachelor degree had been kept. The author paid attention to the fact that there is a differentiation between Masters practitioners and Masters scholars. Master training meets national traditions of the country, but in addition, there is a difference in the Master's training at various universities in the same country.